Trust Management Methodology and Agents Simulations Framework for Conflict Research. Issue 4 (7th February 2023) - Trček, Denis
Abstract: Trust plays a pivotal role in numerous humans' interactions, and it affects relationships ranging from individuals to interstate levels. Any conflict and its resolution can therefore benefit from insights into trust dynamics. The deployment of computational trust management methods and agent technologies provide promising options. They have already been successfully applied in many domains, while in conflict research (and possible resolution policies) they are rather unexplored. This research paper therefore presents an approach that is based on a formalized, anthropocentric trust management method. It deploys it accordingly in agents' simulations to obtain new insights into the dynamics of trust in cooperation–conflict interplay, and to enable derivation of strategies for managing societies to drive them toward desired states. Abstract : Trust plays a pivotal role in humans' interactions, ranging from individuals to interstate levels ‐ any conflict could therefore benefit from insights into trust dynamics. As the deployment of computational trust management and agent simulations provides promising options, this paper presents an approach that uses a formalized, anthropocentric trust management method and agents to derive resolution policies for conflict situations.